Combinations of fungicide molecules and nitrogen fertilization revert nitrogen yield reductions generated by Pyrenophora tritici-repentis infections in bread wheat. (July 2019) - Schierenbeck, Matías; Fleitas, María Constanza; Gerard, Guillermo Sebastián; Dietz, Juan Ignacio; Simón, María Rosa
Abstract: Tan spot [ Pyrenophora tritici-repentis (Died.) Drechs., anamorph Drechslera tritici-repentis ) (Died.) Shoem.] is considered one of the main threats affecting wheat world production. Assessing the impact of this disease and its interaction with fungicides mixtures and nitrogen (N) rates would be useful in order to improve the quantification and modeling of crop N dynamics and enhance grain yield and quality. Our study was designed to determine the additive effects of SDHI fungicides (carboxamide) (TSC) to a triazole-strobilurin (TS) mixture under three N fertilization rates on the tan spot progress, green leaf area dynamics, grain yield, N remobilization (NREM), N post-anthesis absorption (NPA), %N in grains and N stored in grains (NG). Our results indicated that reductions in the NREM, NPA and NG caused by tan spot infections would be explained by reductions in the crop growth rate and HAD/FLHAD, that generates a fall in the biomass generation and grain yield. The negative effects of tan spot could be reverted by fungicides and N fertilization combinations. The most efficient disease control was obtained with TSC fungicides in combination with high N doses. Physiological effects of TSC mixtures like broadening green leaf area dynamics are likely responsible for the greater increases in grain yield (+15.8%), NREM (+13.4%), NPA (+41.6%) and NG (+18.1%) with respect to TS under the same N rates (140N). In these work, we reported the first evidence of the overcoming effect of triple fungicidal mixtures in N dynamics in bread wheat under tan spot epidemics. Highlights: Tan spot effects on N dynamics under different N doses and fungicides were addressed. Tan spot reduces wheat growth rate and N accumulation rate. TSC and N fertilization revert tan spot negative effects on N dynamics and yield. Triple fungicide mixtures overcome the double mixture in all parameters analyzed. Quantification of crop N dynamics could be useful in order to enhance grain quality.